The Effect of Disease and Harvesting on The Dynamics of Prey-Predator System - Satar , Huda Abdul (Iraqi Journal of Science, 2022)
In this paper an eco-epidemiological system has been proposed and studied analytically as well as numerically. The boundedness, existence and uniqueness of the solution are discussed. The local and global stability of all possible equilibrium point are investigated. The global dynamics is studied numerically. It is obtained that system has rich in dynamics including Hopf bifurcation.